1992
DOI: 10.1161/01.hyp.19.6.549
|View full text |Cite
|
Sign up to set email alerts
|

Salt-dependency of endothelin-induced, chronic hypertension in conscious rats.

Abstract: The effect of salt intake on the hypertensive response to long-term infusion of endothelin-1 was investigated. Chronically instrumented male Sprague-Dawley rats (325-375 g) were used in a 15-day protocol that included 3 control days followed by 7 days of endothelin-1 infusion at 5.0 pmol • kg" 1 • min" 1 and 5 days of recovery. Rats were maintained on either a normal sodium chloride intake (2.0 meq Na + per day; normal sodium) or a high sodium chloride Intake (6.0 meq Na + per day; high sodium) throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
1
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
4
30
1
1
Order By: Relevance
“…Phe (10 Ϫ5 mol/L) caused an increase in 45 Ca 2ϩ influx that was greater in NS/ET (27.9Ϯ1.7) than in NS (20.1Ϯ1.8) rats and further enhanced in HS/ET (35.2Ϯ1.8) compared with HS rats (21.8Ϯ1.9 mol/kg/min). The Phe-induced 45 Ca 2ϩ influx-stress relation was not different between NS and HS rats, but was enhanced in ET-infused rats particularly those on HS. The enhancement of the 45 Ca 2ϩ influx-active stress relation in ET-infused rats was not observed in vascular strips treated with the protein kinase C inhibitor GF109203X or calphostin C (10 Ϫ6 mol/L).…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…Phe (10 Ϫ5 mol/L) caused an increase in 45 Ca 2ϩ influx that was greater in NS/ET (27.9Ϯ1.7) than in NS (20.1Ϯ1.8) rats and further enhanced in HS/ET (35.2Ϯ1.8) compared with HS rats (21.8Ϯ1.9 mol/kg/min). The Phe-induced 45 Ca 2ϩ influx-stress relation was not different between NS and HS rats, but was enhanced in ET-infused rats particularly those on HS. The enhancement of the 45 Ca 2ϩ influx-active stress relation in ET-infused rats was not observed in vascular strips treated with the protein kinase C inhibitor GF109203X or calphostin C (10 Ϫ6 mol/L).…”
mentioning
confidence: 69%
“…The tissues were transferred to the respective radioactive 45 Ca 2ϩ labeled solution (specific activity, 2 Ci/mL; ICN) for 90 sec. Preliminary experiments have shown that the relationship between Ca 2ϩ uptake versus time is linear during 15-, 30-, 60-, and 90-second exposures to the 45 Ca 2ϩ label. The tissues were transferred to ice-cold Ca 2ϩ -free (2 mmol/L EGTA) Krebs for 45 minutes to quench extracellular 45 Ca 2ϩ label.…”
Section: Ca 2؉ Influxmentioning
confidence: 99%
See 3 more Smart Citations